You are on page 1of 3

04 EM – 051 – pr 05: The time-averaged potential of a neutral hydrogen atom is given by

:

Φ(r ) =

q exp( −α r ) (1 + 1 α r ) 2 4πε 0 r

[I.1]

…where “q” is the magnitude of the electronic charge, and α −1 = 1 a0 = 1 [ Bohr radius] . 2 2 Find the distribution of charge (both continuous and discrete) that will given this potential. Interpret your result physically. Gauss’s law in integral form and divergence theorem results in differential Gauss-law:

∇ • E = ρ / ε0
That the electric field is conservative/irrotational implies E = −∇Φ , and this makes [I.2] into:

[I.2]

∇ • E = −∇ • (∇Φ ) = −∇ 2Φ =

ρ ε0

ρ = −ε 0∇ 2Φ = −ε 0∇ r ,θ ,φ 2Φ

[I.3]

Looking at the time-averaged potential [I.1], we see it is a function only of “r”, so angular derivatives of the full Laplacian (as in [I.3]) vanish. Thus, we only need the radial component of Laplacian:

∇ r 2Φ =
Rearrange the given potential [I.1] so that the trivial
4πε 0 q

1 ∂  2 ∂Φ  r  r 2 ∂r  ∂r 
is away from the functions of “r”,

[I.4]

4πε 0 1 Φ( r ) = 1 e −α r (1 + 1 α r ) = ( 1 + 2 α ) e −α r = f ( r ) ⋅ g (r ) r 2 r q
Thus, we are to apply ∇r 2 of [I.4] to the product of functions ; what results are binomial coefficients in ∇ ,

[I.5]

∇2 ( f ⋅ g ) = ∇ • ∇( f ⋅ g ) = ∇ • ∇f ⋅ g + f ⋅ ∇g = ∇ 2 f ⋅ g + f ⋅ ∇2 g + ∇f • ∇g + ∇g • f = ∇ 2 f ⋅ g + f ⋅ ∇ 2 g + 2∇f • ∇g [I.6]
1 Calculating ∇f , ∇g , ∇ f , and ∇ g in which, by [I.5], f = 1 + 2 α and g = e −α r , and using [I.4] to handle “g” and r

(

)

(

)

2

2

∇2 1 ≡ −4π ⋅ δ 3 ( r ) to handle “f”, r
∇f = ∂ 1 1  −1 ˆ ˆ  + α r = 2 r ∂r  r 2  r ∇g = ∂ −α r ˆ ˆ ( e ) r = −α e−α rr ∂r
[I.7]

1 1  ∇ 2 f = ∇ 2  + α  = −4π ⋅ δ (x − x′) = −4π ⋅ δ 3 ( r ) r 2 
∇2 g =

[I.8]

1 ∂  2 ∂ −α r  −α ∂ 2 −α r e = 2 ( r e ) = −α ( 2re −α r − r 2α e−α r ) = (α 2 − 2rα ) e−α r r 2 r ∂r  ∂r r2  r ∂r

[I.9]

Putting [I.7], [I.8], and [I.9] together a la [I.6] to constitute the Laplacian of the product [I.5], 4πε 0 2 1 ˆ ˆ ∇ Φ ( r ) = ( 1 + 2 α ) (α 2 − 2rα ) e −α r − 4π ⋅ e −α rδ 3 ( r ) + 2 ⋅ −21 r • ( −α e −α rr ) r r q

( )

[I.10]
−α r

=

(

1 r

α −2r + α −
2

2

α

1 2

3

α2
r

− 4π ⋅ δ ( r ) + 2 r 2 e

3

α

)

−α r

= ( α − 4π ⋅ δ ( r ) ) e
1 2 3 3

Q = ∫ ρ ( x′) ⋅ d 3 x′ = ∫ q (δ 3 ( x ) − 81 α 3e −α r ) d 3 x = q π 0 ∞ ( ∫ δ (x ) ⋅ d x − 3 3 1 2 α 3 ∫ e −α r r 2 ⋅ dr 0 ∞ ) [I. Chabysheva invites us to remember the definition of the gamma function.5 . checking our answer: The hydrogen atom is charge neutral.6 0.3] is.15] Plotting this charge density [I.2 0. so [I.8 0. ∫ Q = q (1) − 1 α 3 α13 ∫ e −α r r 3−1 ⋅ d (α r ) = q (1 − 1 Γ(3) ) = q (1 − 1 2!) = q (1 − 1) = 0 2 2 2 0 ( ∞ ) [I. using d 3 x ′ = 4π r 2 ⋅ dr . [I. ρ = −ε 0∇2Φ = −ε 0 Realizing q 4πε 0 ( 1 2 α 3 − 4π ⋅ δ 3 ( r ) ) e −α r = −q 1 3 ( 2 α − 4π ⋅ δ 3 (r ) ) e−α r 4π [I.1 0.length units: Bohr radii.12] and letting δ ( r ) ≈ e −200 r .9 [I.12] should integrate to zero over all space.5 x 0.14] Thus.11] ∫ 0 +δ x 0 −δ x δ ( x ) ⋅ e − ax ⋅ dx = ∫ 0+δ x 0−δ x δ ( x ) ⋅ dx .5 proton + electron cloud electron cloud alone 1 0 0.3 0. "alpha" proton alone − exp( − x) exp − 200⋅x 2) ( 2 exp (− 200⋅x ) −exp ( − x) 0 0. and − q απ e 8 electron cloud.7 0.11] simplifies to.13] To integrate ∫ ∞ 0 e −α r r 2 ⋅ dr .16] .13] becomes. our instructor Dr. ρ=   − q 1 3 −α r α3 α e − 4π ⋅ δ 3 ( r ) ) = q  δ 3 ( r ) − e −α r  (2 4π 8π   3 [I.12] −α r is the charge density of the surrounding Clearly: q ⋅ δ 3 ( r ) is the charge density of the kernel-nucleus. [I. 1 2 . Γ(n ) ≡ ∫ x n −1e − x ⋅ dx = (n − 1)! 0 ∞ [I. after effecting δ 3 (x ) ⋅ d 3 x = 1 .charge density units: 4*pi*q/epsilon[0] 0.4 0.The charge density by [I.

5] with r > 0. This results in.Alternate solution The shorter way.18] 1 So. would be: first consider applying −ε 0∇ to [I.20] constitute both charge densities! .17].19]. consider the limit r → 0 . except we bear in mind the formula ∇2 ( 1 ) ≡ −4π ⋅ δ ( r ) . −ε 0∇2 4πε 0Φ 1 1 = −ε 0∇2 (1 − α r )( 1 + 1 α ) = −ε 0∇2 ( 1 + 2 α − α − 2 α 2 r ) = −ε 0∇2 ( 1 − 1 α 2r − 1 α ) r r r 2 2 2 q 1 r [I.19] becomes.18] and [I. −α r 1 ∂  2 ∂ ( e ( 1 + 1 α ))  1 ∂ 2 r 2 r −α e −α r ( 1 + 1 α ) + e −α r −21 −ε 0∇ Φ = −ε 0 2  r  = −ε 0 2 r 2 r r ∂r  r ∂r ∂r  1 ∂ 1 = ε 0 2 e −α r (α r + 1 α 2r 2 + 1) = ε 0 2 e −α r −α (α r + 1 α 2 r 2 + 1) + α (1 + α r ) 2 2 r ∂r r 1 ρ (r) −ε 0∇2Φ = αε 0 2 e −α r ( − 1 α 2 r 2 ) = − 1 α 3ε 0e −α r = 4πε 0 2 2 r q 2 2 ( ( )) ( ) [I. we have >> r . From there.12] (in units where 4πε0 = 1 ).17] Solving for ρ ( r ) in [I. ρ ( r ) = − 81 qα 3e −α r π [I.17]. then.20] Bam: [I. r −ε 0∇ 2Φ = −ε 0∇ 2 1 + ε 0 r 1 ∂  2 ∂ α αε 0 ∂ 2 ( r ) ⋅ 0 = 4πε 0 ⋅ δ ( r ) r  2 (α ⋅ 0 − 1) = 4πε 0 ⋅ δ ( r ) + 2 2 r ∂r  ∂r  2 r ∂r [I. we get. we effect the same rigamarole at the beginning of [I. so we may discard that term too.19] In [I. where we may let e x ≈ 1 + x . Now. for r → 0 . blind application of the operator −ε 0∇2 yields the second term in [I. which is in our best interest for the exam. and [I.